2022
DOI: 10.1021/acssensors.2c01003
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Counting-Based Measurement for Paper Analytical Devices and Their Application

Abstract: This work introduces the concept of a counting-based measurement on paper analytical devices (cPADs) to improve the utilization of numerous reactions. The design of cPADs consists of two layers of paper substrates; the first layer contains a central sample zone combined with a radial surrounded by 12 detection zones that are predeposited with the various reagents, and the second layer acts as a connection channel between the sample zone and each detection zone. The solution can vertically flow from the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In this study, the number of colored bars can be employed to identify the amount of H 2 O 2 . A similar study was also reported by Khachornsakkul et al [27], who employed a novel counting-based instrument-free signal readout device designed to detect the Cu 2+ and carbaryl (CBR) in real samples. The paper analytical device, depicted in Figure 3, is constructed with two layers of filter paper; the initial layer is equipped with twelve detection zones, all of which have been pre-loaded with specific reagents to measure Cu 2+ and CBR, and the subsequent layer is used to establish a pathway between the sample and detection zones.…”
Section: Counting-based Signal Readout Technologysupporting
confidence: 65%
“…In this study, the number of colored bars can be employed to identify the amount of H 2 O 2 . A similar study was also reported by Khachornsakkul et al [27], who employed a novel counting-based instrument-free signal readout device designed to detect the Cu 2+ and carbaryl (CBR) in real samples. The paper analytical device, depicted in Figure 3, is constructed with two layers of filter paper; the initial layer is equipped with twelve detection zones, all of which have been pre-loaded with specific reagents to measure Cu 2+ and CBR, and the subsequent layer is used to establish a pathway between the sample and detection zones.…”
Section: Counting-based Signal Readout Technologysupporting
confidence: 65%
“…Conversely, as the sample volume exceeded 30.0 μL, the analytical signals for both detections gradually decreased. This decline can be attributed to the larger sample volume potentially leading to solution leakage from the paper substrate . We thus selected the sample volume of 25.0 μL as an optimal level for achieving the simultaneous detection of E.…”
Section: Resultsmentioning
confidence: 99%
“…This decline can be attributed to the larger sample volume potentially leading to solution leakage from the paper substrate. 42 We thus selected the sample volume of 25.0 μL as an optimal level for achieving the simultaneous detection of E. coli and NO 2 − . Likewise, we introduced a sample volume of 5.0 μL into the sample inlet for five times to assess the impact of the number of sample drops on our assay.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Initially, 2 mL of the sensory solutions of T1 or T2 in THF (0.25 mM) were dropped directly onto filter sheets. [39][40][41] Subsequently, images of the T1 or T2 paper-based device were dropped before being exposed to (10 and 100 mM) TNT solutions for 5 minutes. Additional photographs were obtained using a portable UV lamp with an excitation wavelength of 365 nm.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%